A review on exergetic analysis and assessment of various types of engines. (4th March 2010) - Caliskan, Hakan; Tat, Mustafa Ertunc; Hepbasli, Arif
This study presents a review on energy and exergy analysis of Otto and Diesel engines. Calculation methods of the analysis are discussed in detail. Previous studies, from 1963 to 2008, are chronologically listed and studied. The test engines had different cylinder numbers, speeds and rated powers. Engine specifications and test bench schematics are given in tables and figures. The best exergetic efficiency is achieved with four-stroke, four-cylinder, turbocharged Diesel engines at about 30% excepting to stationary Diesel engine. It is considered that exergetic efficiency can be higher at lower speeds between 1140 1/min and 2200 1/min.